Neurological Problems during Hajj Season: Review - Alkhotani, Amal; Alamoudi, Nada M.; Almuwallad, Norah T.; Abu Zahirah, Mohammad O.; Alatawi, Nouf A. (Journal of Liaquat University of Medical & Health Sciences, 2023)
Worldwide gatherings at religious festivals raise the possibility of disease transmission among attendees and the local populace. The enormous gathering of pilgrims may impact the country's health system. Infectious diseases with epidemic characteristics threaten global health security, demonstrating the significance of preparedness for any public health catastrophe. This literature review describes the extensive neurological disorders related to hajj pilgrims and the importance of preventive methods to control these diseases. Our systematic review was conducted from many sources, including credible websites and journals. We found about 23 articles about the most common neurological disease in hajj pilgrims. A clear result was observed about increased incidents of meningitis as a global health neurological disease related to hajj pilgrims of total PubMed indexed publications studies, and one review article was done in 2019. This review study summarizes the neurological health challenge from infectious, non-infectious to stroke mimics presentation and the heatstroke prevalence in Hajj and the process of how the body adaption to heat stress may influence the body systems and brain function to be reported the most common presentation may mimic to a neurological cause. KEYWORDS: Religious Festivals, Neuro-infectious, Stroke, Heatstroke, Hajj, Makkah